Analisis Peramalan Penjualan dan Keuntungan Usaha Peternakan Kambing dan Domba di CV Amanah Saebur Kecamatan Tambun Selatan, Kabupaten Bekasi - Yulita, Rona; Abadi, Slamet; Wulandari, Yeni Sari (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
Types of animals sold in CV. Amanah Saebur is goat and sheep whose sales fluctuate due to erratic demand from consumers which causes companies to be in a condition of excess or shortage of livestock so that they lose the opportunity to get maximum profit. The purpose of this study is to find the best forecasting technique for goat and sheep sales, make sales forecasting rates and calculate the profit from sales forecasting during June to November 2023 for goats and sheep in CV. Amanah Saebur. The method used is descriptive analysis with a quantitative approach using Single Exponential Smoothing, Double Exponential Smoothing, Multiplicative Decomposition and ARIMA forecasting techniques. The results of the study showed that the Multiplicative Decomposition technique is the best forecasting technique with the smallest Mean Squared Deviation (MSD) value of 20.1104. The results of the forecasting rate of goat and sheep sales were 571 heads with an average of 95 heads per month. Total profit from sales for 6 months amounted to Rp516,378,504.00 with an average profit per month of Rp86,063,084.00. The results of sales and profit forecasting can be an illustration for the company in determining the right decisions in the future and can be used as a reference in conducting production planning.